Pengaruh Balance Exercise (Latihan Keseimbangan) Terhadap Resiko Jatuh pada Lansia di BSLU Meci Angi Kota Bima - Ayatullah, Ayatullah; Wahidah, Wahidah (Barongko: Jurnal Ilmu Kesehatan, 2023)
The risk of falling is an incident reported by sufferers or families who saw the incident, which resulted in a person suddenly lying down, sitting on the floor or a lower place with or without loss of consciousness or injury. Balance exercises can reduce the frequency of falls in the elderly, if done with an optimal frequency of 3 times a week for 2-3 weeks. The purpose of this study was to determine the effect of balance exercise on the risk of falling in the elderly at BSLU Meci Angi Kota Bima in 2023. This study used the One Group Pre Test-Post Test Design. The population of this study was 30 elderly people. The sampling technique used Purposive Sampling with a total sample of 24 people and used the Wilcoxon Signed Rank Test. The instrument in this study used observation sheets in the form of an assessment of the risk of falling in Geriatrics and management observation sheets. The results of the fall risk analysis obtained sig pValue = 0.000 <α 0.05, meaning that there is an influence of Balance Exercise on the Risk of Falling in the Elderly BSLU MeciAngi Kota Bima in 2023. The conclusion in this study is that there is a significant change in the risk of falling before and after giving Balance Training Against the Risk of Falling in the Elderly at BSLU MeciAngi Kota Bima).